Compartilhamento de moléculas de quorum sensing para sinalização e tolerância de Pseudomonas sp. a herbicidas como potencial para adaptação a diferentes condições de estresse ambiental - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
Quorum sensing (QS) is a bacterial communication system that allows bacteria to monitor the surrounding cell population density mediated by means of chemical signaling molecules called autoinducers and, from that, collectively coordinate gene expression, initiating important physiological changes for its survival. In this way, bacteria are able to survive in environments where conditions change constantly, due to the genetic adaptation that results from the flexibility of expression of their genes. In the environment, bacteria have to deal with several toxic components. The introduction of pesticides, for example, contributed to pest control and increased agricultural production. But although its use in agriculture has benefited crop productivity, concerns have arisen about the adverse effects of these pollutants. Exposure of bacteria to toxic components can lead to changes in cell metabolism, growth, enzyme activity and decreased diversity of these bacteria. When exposed to stressful environments, they need changes in physiological and structural processes to survive. In this way, several species of bacteria use important adaptive strategies coordinated by the QS to contribute to the increase of their capacity in terms of survival under different environmental conditions. However, it is still unclear in the literature whether QS can be used by bacteria to coordinate collective behavior in the population in response to herbicides. Therefore, the objective of this work was to evaluate whether there is a QS response system in a Pseudomonas sp. modulated by the presence of herbicides. A strain of Pseudomonas sp. from water storage tanks used for washing pesticide packaging and Heat herbicides containing the active ingredient saflufenacil, Boral 500 SC containing sulfentrazone, Roundup Transorb R containing glyphosate, Aminol 806 containing 2,4-D and Atectra containing dicamba. An extraction of the signaling molecules was carried out and subsequently analyzed in liquid chromatography coupled with mass spectrometry. Here we show that in the presence of the Heat and Roundup Transorb R herbicides, the strain seems to share a regulatory control by the same QS signaling molecules to control the oxidative stress produced by both the energy production system and the herbicide toxicity. In the presence of the herbicides Boral 500 SC, Aminol 806 and Atectra, a profile of molecules was observed that are involved in different stages of biofilm formation and their signaling may be an indication that the lineage is modulating the formation of biofilm as an adaptive strategy to withstand the stress of these herbicides. Thus, bacterial QS can play an important role in adapting to environmental stresses and possibly bring contributions to the study of herbicide bioremediation.
Keywords: Adaptação bacteriana; Comunicação bacteriana; Comunicação bacteriana; Herbicidas; Microbiologia Ambiental; Espectrometria de massas; Bacterial adaptation; Bacterial communication; Environmental Microbiology; Environmental Microbiology; Herbicides; Mass spectrometry; CNPQ::CIENCIAS BIOLOGICAS